2013
DOI: 10.2169/internalmedicine.52.8158
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia and Lymphocytopenia are Predictive Risk Factors for In-hospital Mortality in Patients with Tuberculosis

Abstract: Objective The aim of this study was to clarify the association between nutritional state on admission and in-hospital death in tuberculosis (TB) patients, including a high proportion of elderly patients. Methods A retrospective cohort study of 246 TB patients was conducted. The serum albumin concentrations and peripheral blood lymphocyte counts were measured on admission, and the primary outcome of interest was in-hospital death. Patient mortality was categorized into two groups: TB death and non-TB death. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 11 publications
1
22
1
3
Order By: Relevance
“…Several nutritional factors are also known to be involved in poor prognosis in TB including miliary TB (1,10,11,29). Our study found no significant difference in mortality associated with BMI.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Several nutritional factors are also known to be involved in poor prognosis in TB including miliary TB (1,10,11,29). Our study found no significant difference in mortality associated with BMI.…”
Section: Discussioncontrasting
confidence: 43%
“…Explanation for the correlation between the increase in NLR and poor outcome has not yet been clarified. Although lymphopenia has been reported to be associated with poor prognosis in several previous analyses on TB (1,10,29), NLR has not been investigated in miliary TB. In cancer patients, some studies hypothesized that relatively low lymphocyte counts are associated with a poor response to chemotherapy in relation to cell-mediated immunity (22,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoalbuminemia has been used as a predictive risk factor for mortality in human TB patients as a reflection of nutritional status and disease chronicity [40]. Increased albumin values were observed in the experimentally infected rhinoceroses, however, albumin and total protein values increased significantly in uninfected boma adapted rhinoceroses [20], therefore these changes were probably unrelated to M .…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of M. tuberculosis leads to poisoning symptoms affecting patients' appetite and inducing fever. Insu cient protein intake and increased metabolism due to fever can reduce serum protein levels, leading to hypoproteinemia 13 ; immunity function and compliance to systematic anti-tuberculosis treatment are really poor for elderly patients, most are complicated with huge abscess, sinus, and dead bone formation, and the value of conservative treatment is limited; tuberculosis recurrence is relatively high after the surgical intervention; in elderly patients with severe osteoporosis, multiple fractures of the thoracolumbar spine may coexist with tuberculosis. Most patients had severe kyphosis and/or neurological dysfunction when they sought medical care.…”
Section: Discussionmentioning
confidence: 99%